1998
DOI: 10.1017/s0890060498123016
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge-based system integrated with numerical analysis tools for aircraft life-cycle design

Abstract: An integrated design and manufacturing approach allows economic decisions to be made that reflect an entire system design as a whole. To achieve this objective, we have developed and utilized integrated cost and engineering models within a focused design perspective. A framework for the integrated design of an aircraft system with a combined performance and economic perspective is described in this article. This framework is based on the concept of Design Justification using a Design-for-Economics app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It was concluded that the compressive strengthσ c degrades exponentially. In the context of isotropic materials, the equationσ =σ max e Bvp (6) has elevated to describe this behavior, whereσ max is the strength at zero porosity, v p is the volume fraction of pores and B is an empirical constant that depends on orientation, shape and size of the pores.…”
Section: Strength Reduction Due To Porositymentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the compressive strengthσ c degrades exponentially. In the context of isotropic materials, the equationσ =σ max e Bvp (6) has elevated to describe this behavior, whereσ max is the strength at zero porosity, v p is the volume fraction of pores and B is an empirical constant that depends on orientation, shape and size of the pores.…”
Section: Strength Reduction Due To Porositymentioning
confidence: 99%
“…The adjustment of the allowables due to porosity was estimated according to Equation (6). The value of B = −3.14 was adopted from Uhl et al [23] who performed a number of test series for a 16 ply quasi-isotropic carbon/epoxy laminate.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The cost for these maintenance practices totals up to 11% of the total life cycle cost of the aircraft [6]. For a fleet of 108 Boeing 737 airplanes, this amount exceeds $4 billion over a 25 year life cycle [7].…”
Section: Motivationmentioning
confidence: 99%
“…In different stages of a product's life cycle, knowledge is generated and, where possible, recorded. Such knowledge is useful when planning products (Marx et al, 1998). This knowledge can form the basis for design (computer-aided design models and process descriptions); it can also be used to avoid decisions that led to issues in the product's life cycle (as reflected in change requests or incident reports).…”
Section: Introductionmentioning
confidence: 99%